Productivity in the construction industry in the Republic of South Africa: a holistic approach to resources utilization - Lampert, Harry (My University, 1990)
The productivity of the construction industry is recognised internationally as being of a low order, and the productivity of the South African construction industry rates below that of the first world countries. The purpose of the research reported in this thesis was to Identify the major causes of the low productivity; the reasons for the industry’s intractability; and to develop proposals for the improvement of productivity through improved utilization of the industry’s resources. An extensive review of site practices revealed that a major factor responsible for the lack of productivity is the inadequate awareness on the part of management and supervisory staff of the need for and the techniques of effective resource utilization. Contributing to this failure by management are inadequate procedures for the measurement of productivity, for the planning of labour requirements; for the control of labour and materials; and for maintaining communication with, and motivation of the workforce. The author’s thesis is that improvement in productivity can only be achieved through the analysis of the problems and the synthesis of a solution on the basis of a holistic approach. It is fundemental to this thesis that a piecemeal approach to productivity cannot lead to overall improvement in productivity. On the basis of an analysis of the construction process the author has developed an interactive model illustrating the role of the many components, including the management functions, and their influence on productivity. (Abbreviation abstract)
A thesis submitted to the Faculty of Architecture, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy.
Keywords: Construction industry -- South Africa -- Management.; Employee motivation -- South Africa.; Resource allocation.